Opening the record of science: making scholarly publishing work for science in the digital era - Boulton, Geoffrey (Septentrio Conference Series, 2020)
See RECORDING. There is increasing concern about the extent to which the modern system of scientific and scholarly publishing serves the best interests of science. The International Science Council, as the global voice for science, and with its membership of 40 international scientific unions and associations and 144 national members, including national academies and research councils, is pursuing a major new initiative on this topic. This sets out a series of durable principles for scientific and scholarly publishing and analyses the extent to which current publishing regimes are consistent with these principles. It identifies serious deficits in the inhibition of access to the record of science, in global inclusion and innovation, in metrics that stimulate perverse behaviour and in the emerging shift of control of the research cycle into commercial hands. A series of virtual meetings involving the international science community, as represented by the Council’s members, will discuss these issues in September 2020, with the intention of creating an international coalition for action and change that will includes key stakeholders, including the library, funding and university communities. It is vital that the novel capabilities offered by the digital revolution are harnessed to disseminate science more efficiently and effectively to the global public good.